Chos-rje Gtsaṅ-pa Rgya-ras kyis mdzad paʼi Dge sbyor bdun paʼi smon lam - Gtsaṅ-pa Rgya-ras Ye-śes-rdo-rje, 1161-1211 (ʼBrug chen gduṅ sras, 1970)
Prayer of the Drukpa Kargyudpa sect of Tibeatn Buddhism.